Procedures for Measuring Excreted and Ingested Calories to Assess Nutrient Absorption Using Bomb Calorimetry. Issue 12 (7th October 2020) - Basolo, Alessio; Parrington, Shannon; Ando, Takafumi; Hollstein, Tim; Piaggi, Paolo; Krakoff, Jonathan
Abstract : Objective: With the upsurge in interest in the gut microbiome, complete and accurate measurement of ingested calories and calories lost through excreted stool is crucial for assessing the effect of the microbiota on nutrient absorption. Methods: Measurement of ingested and excreted calories was conducted over 3 days. Meals were made in duplicate: one was given to the participant, and one was used for the measurement of calories. Stool was marked by nonabsorbable dye ingested prior to and at the end of each 3‐day diet period and was collected for caloric assessment from the appearance of the first dye marker until the appearance of the second dye marker. Results: Stool calories per gram for pellets were 4.91 ± 0.06 kcal/g. The mean stool calorie loss as a percentage of ingested calories was 7.3% ± 1.6% (range, 6.6%‐8.5%). The stool measurement of kilocalories per gram was not associated with the total measured stool calories or with stool weight ( P = 0.2 and P = 0.2, respectively) over the 3‐day period. However, the weight of stool samples during each dietary intervention was positively associated with the calorie loss in stool ( r = 0.58, P < 0.0001). Conclusions: Our methods provide a direct measure of ingested calories and stool calories needed to accurately assess relative stool calorie loss as a measure of nutrient absorption. The weight of stool samples across the marked diet period is crucial to determining total stool calories.